Corrective habeas corpus and its influence on the - Espinosa Encarnación, Marbelle Sofía (2024)
Corrective habeas corpus, as a jurisdictional guarantee, focuses on the protection of the rights of people deprived of liberty. These people face serious limitations in the exercise of their rights on a daily basis. The State, as the main custodian and guarantor, has the exclusive responsibility of providing the necessary means and resources to prevent the violation of these rights. The objective of this study is to analyze the origin of corrective habeas corpus for the modulation of the custodial sentence from the jurisprudential precedents established by the Constitutional Court of Ecuador. The methodology used for this study responded to a qualitative investigation where, in addition to using the dogmatic legal and interpretative method of the constitutional norm. The results obtained demonstrated that corrective habeas corpus is sufficient to modulate the custodial sentence under the strict established assumptions.